Improving wear performance, physical, and mechanical properties of iron sand/epoxy composite modified with carbon powder - Apriliani, Nurul Fitria; Wirawan, Willy Artha; Muslimin, Mukhlis; Ilyas, R.A.; Rahma, Muchamat Ardistya; Agus Salim, Alfi Tranggono (Elsevier, 2024)
This study was conducted to investigate the usage of iron sand as composite reinforcement. The addition of carbon powder with variations of 15 wt, 20 wt, and 30 wt is expected to enhance the interfacial bond between iron sand and epoxy matrix to be better. Physical and mechanical properties of the composite were investigated using a wear resistance test Pin on Disc method, shore-D hardness, bending test, X-ray diffraction (XRD), Fourier Transform Infrared (FTIR) and Scanning Electron Microscope (SEM). The results showed an increase in wear resistance and mechanical properties of composite due to the addition of carbon powder. This was confirmed by the fact that the HCP composite with 30 wt carbon powder showed a good increase in wear resistance but a reduction in flexural properties and hardness values. Meanwhile, the LCP composite with 20 wt carbon powder was recommended in terms of good flexural properties. The increased mechanical properties of composite were supported by composite crystallinity index value recorded to be 59.45 from the XRD test. SEM analysis showed better dispersion and interfacial bonding for carbon powder and iron sand in the composite matrix. These results are expected to contribute to the new development of composite brake pad. © 2024 The Authors